Use of the ﬂying ash in the dosing of the concrete as a substitute for the cement - Huaquisto Cáceres, Samuel (2018)
Concrete is the most common material used in most civil works because it is a highly resistant and with material steel has a good structural behavior, its production is used as the main cement component, which directly affects the cost , which is why it seeks to reduce the amount of cement with the addition of fly ash, which is a pollutant, waste of power plants. The objective was to dose mixtures of added fly ash as a substitute for the cement in such a way that it does not diminish the resistance of this one and to find the optimal dosage. The material and method used is normal concrete with fly ash additions to the design in proportions of 2.5%, 5.0%, 10.0% and 15.0% for breakages at 7, 14 and 28 days. The results indicate that after 28 days have resistances averaging 221kg/cm2 for both normal concrete as well as concrete with fly ash 2.5%, 231kg/cm2 for 5.0%, 200kg/cm2 to 10.0% and 192kg/cm2 for 15% of fly ash respectively. In conclusion fly ash it improves concrete strength in a range from 3% to 6% beyond these values reduces the strength of concrete, so it can be harmful.